1983
DOI: 10.1007/bf01907319
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of ammonium nitrate

Abstract: The reproducibility of the DTA curves of ammonium nitrate as functions of its grain size and the atmosphere during the measurements was studied with a derivatograph. The temperatures and the areas of the peaks assigned to the modification transitions IV --, III (peak 1), Ill -+ II (peak 2) and II --* I (peak 3) were evaluated. It was found that for some unground samples the area of peak 2 decreases markedly. It has been verified that in an atmosphere of moist air the temperature of peak 1 is lowered. The tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Further increase in moisture content, in the investigated interval, does not influence the temperatures observed. The temperatures determined with this technique under the given conditions agree with those in the literature [1][2][3][4]16] (Fig. 2).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Further increase in moisture content, in the investigated interval, does not influence the temperatures observed. The temperatures determined with this technique under the given conditions agree with those in the literature [1][2][3][4]16] (Fig. 2).…”
Section: Resultssupporting
confidence: 84%
“…The shapes of the DTA curves and the temperatures of the crystal transformations for ammonium nitrate generally agree well with the literature data [2,4,10,12,15], but in the case of [1] only for the samples with higher water contents. Brown and McLarsen [1] have suggested that the IV ~IlI phase transformation takes place only in the presence of moisture, via a dissolution and recrystallization mechanism involving drastic structural change.…”
Section: Resultssupporting
confidence: 76%
“…Unless specified, thermal properties of solid ammonium nitrate are used for the aerosols and those of germanium are used for the substrate (Table I). [25][26][27] The time-dependent temperature profile in the surrounding air is obtained by having the COMSOL Multiphysics software solve the thermal diffusion equation (Eq. 1) with boundary conditions set at zero temperature (assuming no convective heat transfer at the surfaces of the aerosol and the substrate).…”
Section: Methodsmentioning
confidence: 99%
“…Inorganic Materials. The reproducibility of the DTA curves of NH4N03 as functions of grain size and atmosphere was studied with a derivatograph (67). Transitions investigated included the IV -* III, III -* II, and II -I.…”
mentioning
confidence: 99%